Cannulation techniques for extracorporeal life support - Pavlushkov, Evgeny (Ann Transl Med, 2017)
The article reviews cannulation strategy for different modes of extracorporeal life support. Technical aspects, pitfalls and complications are discussed for central and peripheral extracorporeal membrane oxygenation (VA, VV, VAV, VVA), biventricular assist device support and extracorporeal CO(2) removal.